Challenging the current model of early‐onset myasthenia gravis pathogenesis in the light of the MGTX trial and histological heterogeneity of thymectomy specimens. Issue 1 (28th January 2018) - Weis, Cleo‐Aron; Schalke, Berthold; Ströbel, Philipp; Marx, Alexander
Abstract: The MGTX trial provided evidence that, in general, thymectomy is beneficial in adult patients up to 60 years of age with anti‐acetylcholine receptor–positive, nonthymomatous myasthenia gravis (MG). This finding supports the long‐held view that the pathogenesis of this type of MG (early‐onset MG (EOMG)) starts inside the thymus, results in the long‐term intrathymic recruitment of autoantibody‐producing B cells and plasma cells, and eventually spreads to the peripheral immune system. However, observed clinical responses to treatment in the MGTX trial were diverse. This might be due to heterogeneous epidemiological and genetic features of EOMG patients and variable durations of corticosteroid treatment before surgery, including a paucity of patients that were corticosteroid naive. Furthermore, the observed histological heterogeneity suggests that a single pathogenetic model may not fully reflect the spectrum of events that modify the course of EOMG. Here, we describe the morphology of the normal and MG‐associated thymus, how to evaluate morphological changes, and the current pathogenetic model of EOMG and discuss how it could be refined by integrating MGTX‐derived histological findings in thymectomy specimens and associated clinical observations.